Comparison of the Effect of Vaginal Misoprostol and Intravenous Oxytocin on Fetal-Neonatal Complications in Primigravid as Who Referred to Shahid Sadoughi Hospital, Isfahan, Iran in 2017 - Mahboubeh Valiani; Zahra Allameh; Parvin Bahadoran; Zahra Mohebbi-Dehnavi; Elahe Amani (Mashhad University of Medical Sciences, 2020)
Background: Oxytocin and misoprostol are used to initiate labor which can sometimes cause complications to the fetus and neonate. The purpose of this study was to determine the combined effect of vaginal misoprostol and intravenous oxytocin on fetal/neonatal outcomes in primigravidas whoreferred to Shahid Sadoughi Hospital, Isfahan, Iran.Methods: This clinical trial study was performed on 102 pregnant mothers in Isfahan Shahid Sadoughi Hospital. The participants were randomly divided into two groups of oxytocin induction with vaginal misoprostol (n=51) and oxytocin alone (n=51). Finally, fetal heart rate decline during labor and delivery, Apgar scoresat1and 5min, presence of meconium, and admission to neonatal intensive care unit (NICU)were evaluated. The data were then analyzed in SPSS software (version 22).Results: The results revealed that the meconium excretion was significantly higher in the intervention group than the control group (P<0.05). The frequency of early deceleration was significantly lower in the intervention group than in the control group (P<0.05). There was no significant difference between the two groups regarding the frequency of late deceleration and variable deceleration in the fetal heart (P>0.05). Frequency of late deceleration and beat-to-beat changes were quite similar in both groups. There was no significant difference in mean Apgar scoresat1 and 5 min between two groups (P<0.05). Frequency of neonatal hospitalization in the intervention group was significantly higher than the control group (P<0.05). Frequency of neonatal need for resuscitation was similar in both groups.Conclusion: According to the results of this study, concurrent use of misoprostol and oxytocin increased neonatal meconium excretion and NICU admission.